2021
DOI: 10.3390/ijms22052516
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Phosphatase Is Implicated in the Control of THP-1 Monocyte to Macrophage Differentiation

Abstract: Monocyte to macrophage differentiation is characterized by the activation of various signal transduction pathways, which may be modulated by protein phosphorylation; however, the impact of protein kinases and phosphatases is not well understood yet. It has been demonstrated that actomyosin rearrangement during macrophage differentiation is dependent on Rho-associated protein kinase (ROCK). Myosin phosphatase (MP) target subunit-1 (MYPT1) is one of the major cellular substrates of ROCK, and MP is often a counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Monocyte differentiation visualized with cGNS MB was compared with that of conventional methods where the change in the gene expression was evaluated by the flow cytometry and PCR. Flow cytometry analysis with CD11B of a macrophage marker 3,65,66 and CD204 tended to increase with time during the differentiation stimulation, and the fluo-rescence intensity was significantly higher than that of monocytes after 48 h (Figures 9A and B). The difference in the phagocytosis property between monocytes and macrophages was experimentally confirmed.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte differentiation visualized with cGNS MB was compared with that of conventional methods where the change in the gene expression was evaluated by the flow cytometry and PCR. Flow cytometry analysis with CD11B of a macrophage marker 3,65,66 and CD204 tended to increase with time during the differentiation stimulation, and the fluo-rescence intensity was significantly higher than that of monocytes after 48 h (Figures 9A and B). The difference in the phagocytosis property between monocytes and macrophages was experimentally confirmed.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The fact that cGNS MB can visualize monocyte differentiation has the potential for further development. In previous papers, cGNS that can incorporate large amounts of MBs have also been prepared. , Taking advantage of the characteristics of cGNS, it is possible to add MBs targeting other differentiation markers, such as the CD11B and CD68 genes, ,, to make the visualization of differentiation using CD204 MB more accurate and confirm the specificity of cGNSMB system for differentiation into not only dendritic cells but also the monocytes. In addition, simultaneous evaluation of cellular function may be possible by using multiple types of MB.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows ROCK activation in untreated FD patients and demonstrates that ERT reduces ROCK activity, underlining the need for early diagnosis and prompt initiation of ERT and, most importantly, the adjuvant antioxidant treatment with GT further significantly reduced MYPT-1 phosphorylation, supporting the positive effect of an additive antioxidant treatment. Notably, EGCG, the most abundant catechin in GT, was shown to promote dephosphorylation of MYPT-1, indicating the reduction of ROCK activity, which is coupled with increased eNOS activity and NO production, to improve endothelial cells' integrity (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The results showing that EGCG increases rather than decreases pMLC20 are quite intriguing, as numerous studies have demonstrated that EGCG induces the activation of MP and the dephosphorylation of pMLC20 [33][34][35]. To uncover the possible mechanisms behind these unexpected events, we assessed MYPT1 gene and protein levels in the absence or presence of EGCG during the adipogenic differentiation of MSCs.…”
Section: Effects Of Egcg On the Msc Cytoskeletal Rearrangement And Ph...mentioning
confidence: 93%
“…Upon the induction of the adipogenic differentiation of B56δ subunit in the PP2A holoenzyme [32] enhances PP2A activity, resulting in the dephosphorylation of the inhibitory sites in MYPT1, thereby activating MP [31,33]. This EGCG→cAMP→PKA→PP2A→MP activation pathway plays important roles in sensitizing melanoma [31] and leukemic cells [34] to anticancer drugs and in differentiating THP-1 monocytes to macrophages [35]. It remains to be examined if the above EGCG-induced phosphatase activatory pathways may also mediate the adipogenic differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%